Strategy Analysis of Increasing Tax Revenue for Two Wheel Motor Vehicles in Medan City - Rahmad Ziady; Erlina Erlina; Sirojuzilam Sirojuzilam (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine and analyze the strategy for increasing tax revenue for two-wheeled motor vehicles in the city of Medan. The research design used is descriptive method, which is a research method that seeks to solve problems by presenting data, analyzing and interpreting it. While the form of this research is qualitative, namely research in which the data is obtained and analyzed in the form of numbers, starting from data collection, data interpretation and the appearance of the results. The secondary data collection method in this research was obtained through literature study by studying literature books and other official documents that have been published by the government of North Sumatra Province, in addition to obtaining secondary data from the variables studied sourced from interviews, data sourced from Regional Tax and Retribution Management Agency and the Central Statistics Agency of North Sumatra Province and the Central Statistics Agency of North Sumatra Province, the Central Statistics Agency of Medan City. From the results of this study, it is found that the factors that influence the obstruction of two-wheeled motor vehicle tax revenue and the factors also strategy to increase the tax revenue of two-wheeled motorized vehicles in Medan City.